2005
DOI: 10.1086/429522
|View full text |Cite
|
Sign up to set email alerts
|

Extreme X-Ray Behavior of the Low-Luminosity Active Nucleus in NGC 4395

Abstract: We present the results of a 17 ks Chandra ACIS-S observation of the nearby dwarf spiral galaxy NGC 4395. Chandra affords the first high-quality, broadband X-ray detection of the active nucleus of this object that is uncontaminated by nearby sources in the field. We find the nuclear X-ray source to be unresolved and confirm the rapid, large-amplitude variability reported in previous studies. The light curve appears to show $11 cycles of a quasi-periodic oscillation with a period of $400 s. If associated with an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(113 citation statements)
references
References 37 publications
7
105
0
1
Order By: Relevance
“…5) by the finding of high-ionization narrow emission lines and broad Balmer emission lines in their optical spectrum (Kunth et al 1987;Filippenko & Sargent 1989). These, together with the detection of hard X-ray emission, indicate the presence of an AGN with a BH mass of M BH ∼ 3 × 10 5 M estimated from the width of the broad emission lines under the assumption that the gas is virialized (Filippenko & Ho 2003;Barth et al 2004;Moran et al 2005;Peterson et al 2005;Vaughan et al 2005;Thornton et al 2008). NGC 4395 has, in addition, a compact radio jet (Wrobel & Ho 2006) and is one of the few dwarf galaxies for which a dynamical BH mass measurement has been possible (M BH = 4 +8 −3 × 10 5 M ; den Brok et al 2015).…”
Section: Dwarf Galaxiesmentioning
confidence: 90%
“…5) by the finding of high-ionization narrow emission lines and broad Balmer emission lines in their optical spectrum (Kunth et al 1987;Filippenko & Sargent 1989). These, together with the detection of hard X-ray emission, indicate the presence of an AGN with a BH mass of M BH ∼ 3 × 10 5 M estimated from the width of the broad emission lines under the assumption that the gas is virialized (Filippenko & Ho 2003;Barth et al 2004;Moran et al 2005;Peterson et al 2005;Vaughan et al 2005;Thornton et al 2008). NGC 4395 has, in addition, a compact radio jet (Wrobel & Ho 2006) and is one of the few dwarf galaxies for which a dynamical BH mass measurement has been possible (M BH = 4 +8 −3 × 10 5 M ; den Brok et al 2015).…”
Section: Dwarf Galaxiesmentioning
confidence: 90%
“…In comparison with other AGN, the X-ray spectrum of NGC 4395 below 10 keV appears to be very hard even after correcting for absorption, Γ ∼ 1.4 (e.g., Shih et al 2004;Moran et al (2005) suggested an even lower value of Γ ∼ 0.6). Despite the relatively low 2-10 keV flux (∼4 × 10 −13 erg s −1 cm −2 ), NGC 4395 was detected by INTEGRAL IBIS (Beckman et al 2006;Bird et al 2007) in 20-40 keV and 40-100 keV bands.…”
Section: Introductionmentioning
confidence: 88%
“…NGC 4395 is a very late-type (Sdm) spiral with no bulge component, whose central stellar velocity dispersion is à < 30 km s À1 . Nevertheless, it has the emission properties of a type 1 active galactic nucleus (AGN), with broad permitted optical and UV emission lines (Filippenko & Sargent 1989;Filippenko et al 1993), a compact radio core (Ho & Ulvestad 2001) with a nonthermal brightness temperature (Wrobel et al 2001), and a pointlike, hard X-ray source ) that is highly variable (Moran et al 1999(Moran et al , 2004Shih et al 2003). Mass estimates based on the H line width-luminosity mass scaling relation and X-ray variability suggest a BH mass of 10 4 10 5 M .…”
Section: Introductionmentioning
confidence: 99%